Family functioning buffers the consequences of the COVID-19 pandemic for children’s quality of life and loneliness - Skeens, Micah A.; Hill, Kylie; Olsavsky, Anna; Ralph, Jessica E.; Udaipuria, Shivika; Akard, Terrah Foster; Gerhardt, Cynthia A. (Frontiers in Psychology, 2023)
COVID-19 resulted in mass quarantine measures early in the pandemic. This disruption of daily life widened inequities and made children one of the most vulnerable populations during the crisis. This national, cross-sectional “COVID-Kids” study collected data from almost 500 parent-child dyads using standardized measures to better understand the effects of COVID exposure and impact on children’s quality of life and loneliness. Data were collected via social media from May to July 2020. According to parent and child-report, U.S. children experienced worse quality of life (p < .0001; d = 0.45 and 0.53) and greater child-reported loneliness (p < .0001) when compared to normative samples. Older children (r = .16, p = .001) and females (r = .11, p = .02) reported greater loneliness. Higher child-reported family relationship scores were associated with better quality of life (r = .36, p < .0001) and less loneliness (r = -.49, p < .0001). Moderated mediation analyses indicated the indirect effect of parent COVID impact on the association between COVID exposure and child quality of life was weaker in the context of better family relationships. Results of this study raise concern for the short- and long-term sequelae of the pandemic on the physical and mental health of children. Healthcare providers and researchers must find new and innovative ways to protect the well-being of children. Strengthening family relationships may buffer the effects of the pandemic and improve overall quality of life in our “COVID Kids.”